Optimal taxation and redistribution in a two sector two class agents' economy - Sheikh Selim (Cardiff University, Cardiff Business School, 2011)
We examine the optimal taxation problem in a two sector neoclassical economy with workers and capitalists. We show that in a steady state of this economy the optimal policy may involve a capital income tax or subsidy, differential taxation of labour income and redistribution. The level and the direction of the redistribution associated with such an optimal policy depends on the pre tax allocation of capital but not on the social weights attached to the different groups of taxpayers. Excess production of consumption goods creates a difference between the social marginal values of consumption and investment which in turns violates the production efficiency condition. Such a difference can be undone by taxing capital income from the consumption sector, and with this optimal policy the government can implement a redistribution scheme where both workers and capitalists bear the burden of distorting taxes. On the contrary, an optimal policy that involves a capital income subsidy in the production of consumption can implement allocations that minimize the relative price difference between consumption and investment that resulted from the excess production of investment goods.
Keywords: C61; E13; E62; H21; 330; Optimal taxation; Ramsey problem; Two Sector Economy; Redistribution; Mehr-Sektoren-Modell; Optimale Besteuerung; Lohnsteuer; Kapitalertragsteuer; Verbrauchsteuer; Einkommensumverteilung; Ramsey-Preis